2020
DOI: 10.1021/acs.est.0c00558
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Arsenic and Antimony Uptake and Tolerance in Toad Tadpoles during Development in Highly Contaminated Wetlands

Abstract: The effects of extreme concentrations of toxic metalloids, such as arsenic (As) and antimony (Sb), on larval amphibians are not well-understood. We sampled Western Toad tadpoles (Anaxyrus boreas) living in As- and Sb-contaminated wetlands throughout their development. Although the tadpoles completed metamorphosis, they accumulated among the highest concentrations of As and Sb ever reported for a living vertebrate (3866.9 mg/kg; 315.0 mg/kg (dry weight), respectively). Ingestion of contaminated sediment had a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…As reported, the existence of MPs in plant–soil systems could change the rhizosphere microenvironment influencing rhizosphere microbial community structures and microbial metabolism activities. ,, For example, Zhou et al indicated that poly­(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) MPs, one of the common PHA biopolymers, could increase specific microbial growth rates and result in higher active microbial biomass . PLA and PHB or their degradation intermediates could be utilized as an extra carbon source by particular heterotrophic microorganisms, thereby affecting the microbial community. , The presence of Sb in soil was also reported to be capable of altering microbial communities . Wang et al documented that both Sb­(III) and Sb­(V) exhibited inhibition effects on bacterial diversities and community structures, thereby downregulating potential nitrification rates, with Sb­(III) revealing stronger impacts than Sb­(V) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, the existence of MPs in plant–soil systems could change the rhizosphere microenvironment influencing rhizosphere microbial community structures and microbial metabolism activities. ,, For example, Zhou et al indicated that poly­(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) MPs, one of the common PHA biopolymers, could increase specific microbial growth rates and result in higher active microbial biomass . PLA and PHB or their degradation intermediates could be utilized as an extra carbon source by particular heterotrophic microorganisms, thereby affecting the microbial community. , The presence of Sb in soil was also reported to be capable of altering microbial communities . Wang et al documented that both Sb­(III) and Sb­(V) exhibited inhibition effects on bacterial diversities and community structures, thereby downregulating potential nitrification rates, with Sb­(III) revealing stronger impacts than Sb­(V) .…”
Section: Resultsmentioning
confidence: 99%
“…18,85 The presence of Sb in soil was also reported to be capable of altering microbial communities. 89 Wang et al documented that both Sb(III) and Sb(V) exhibited inhibition effects on bacterial diversities and community structures, thereby downregulating potential nitrification rates, with Sb(III) revealing stronger impacts than Sb(V). 37 According to previous reports, the presence of Sb could also act as an electric donor or a recipient substrate, leading to alteration of microbial community structures and metabolism.…”
Section: ■ Materials and Methodsmentioning
confidence: 98%
“…When the flow rate is 5 and 10 mL·min −1 , the dynamic adsorption penetration curves of Sb(V) are respectively 116.4% and 144.1% when there is WMF, which compared with no WMF. nZVI accelerates corrosion by WMF, and the produced Fe 2+ promoted the removal of Sb(V) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plastic catalysts, flame retardants, pigments, batteries, glass, and ceramics are just a few of the industries that employ Sb. It has, however, been proven to expose significant threats to human health and ecosystems [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most Sb levels in unpolluted water samples are below 1 μg L –1 . However, serious Sb pollution in waters has also been widely reported. , For example, the streams flowing through the tailing piles of Xikuangshan (Hunan, China) contain high dissolved Sb concentrations of 4.58–29.4 mg L –1 . On the other hand, the World Health Organization and China have set the safe drinking water limit for Sb at 20 and 5 μg L –1 , respectively .…”
Section: Introductionmentioning
confidence: 99%